2013
DOI: 10.1111/php.12212
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod‐Assembled PEGylated Graphene‐Oxide Nanocomposites for Photothermal Cancer Therapy

Abstract: Gold nanorod-attached PEGylated graphene-oxide (AuNR-PEG-GO) nanocomposites were tested for a photothermal platform both in vitro and in vivo. Cytotoxicity of AuNR was reduced after encapsulation with PEG-GO along with the removal of cetyltrimethylammonium bromide (CTAB) from AuNR by HCl treatment. Cellular internalization of the CTAB-eliminated AuNR-PEG-GO nanocomposites was examined using dark-field microscopy (DFM), confocal Raman microscopy and transmission electron microscopy (TEM). To determine the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…Near-infrared (NIR) resonant nanomaterials such as Au nanorods (GNRs) [7,12,13], multi-branched particles [14,15], nanoshells [16], and hollow-shells (HSs) [11,17] are attractive therapeutic agents because they can deliver drugs via non-invasive hyperthermia. NIR light in the range of 700e900 nm has been widely used to locally raise cell temperature, thereby optimizing the photothermal effect [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-infrared (NIR) resonant nanomaterials such as Au nanorods (GNRs) [7,12,13], multi-branched particles [14,15], nanoshells [16], and hollow-shells (HSs) [11,17] are attractive therapeutic agents because they can deliver drugs via non-invasive hyperthermia. NIR light in the range of 700e900 nm has been widely used to locally raise cell temperature, thereby optimizing the photothermal effect [18].…”
Section: Introductionmentioning
confidence: 99%
“…Effective drug delivery by nanocarriers has been intensively investigated using dendrimers [1,2], polymeric micelles [3], liposomes [4,5], carbon-based materials [6e8], magnetic particles [9,10], and noble metal nanoparticles (NPs) [7,11]. Nanocarriers were developed to protect drugs from premature degradation and to enhance drug absorption into specific tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Joo et al assembled GNRs on PEGylated graphene oxide, which lead to both an increase in colloidal stability and a displacement of cytotoxic CTAB by PEG. 224 In vivo studies with A491 epidermal carcinoma cells showed a 60% cell viability after 5 min of radiation under a Xe-lamp (60 W/cm 2 . A separate approach involving thionin-bridged hybrid materials was considered by Zhu et al 225 AuNPs were covalently bonded to reduced graphene functionalized with thionin.…”
Section: Carbon/gold Hybridmentioning
confidence: 99%
“…Gold nanorod-attached PEGylated graphene-oxide (AuNR-PEG GO) nanocomposites were synthesized by Dembereldorj et al and used for photothermal therapy both in in vitro and in vivo. 82 The presence of AuNRs signi¯cantly enhanced the NIR absorption e±ciency of the nanocomposites which resulted in 40% reduction in cell viability of A431 epidermoid carcinoma cells and also reduced tumor volumes in mice. Femtosecond laser beam mediated photothermal destruction of cancer cells was demonstrated by Li et al using graphene oxide nanoparticles (GONs).…”
Section: Photothermal Therapymentioning
confidence: 99%